Impact of Maternal Microbiota Composition on Neonatal Immunity and Early Childhood Allergies: A Systematic Review - Ayah Nabil Al Jehani; Manal Shuaib; Arwa Alsharif; Khlood Abdulaziz Alsubaie; Ayda Khraisat; Abdulaziz Alsharif; Manaf Altaf; Ruba H. Almasry; Amal Mohamed Kayali; Shouq Abdin Abdallah (Pediatric Reports)
Background: The maternal microbiota serve as a key regulator of neonatal immune development and early-life health outcomes. This systematic review aims to find out how the makeup of the maternal microbiota affects newborn immunity and the risk of allergies, identify which microbes are linked to a higher or lower chance of allergies, and assess treatments that could improve newborn immune health. Methods: We conducted a systematic search in PubMed, MEDLINE, and Web of Science, adhering to the PRISMA guidelines. We included randomized controlled trials (RCTs), cohort studies, and observational studies that looked at how the makeup of the maternal microbiota affects newborn immune responses or allergic outcomes in early life. We conducted a systematic search, and the quality of the studies was evaluated using the GRADE system and tools to check for bias (RoB 2, Newcastle–Ottawa Scale, MINORS). Results: We included a total of 74 studies. The main findings showed that having a cesarean delivery and using certain antibiotics during pregnancy increased the risk of allergies, while breastfeeding, taking probiotics, and changing the mother’s diet helped to protect against allergies. Maternal stress had a negative association with the microbiota composition (OR = 1.9–2.4) and neonatal immune regulation. Moreover, the study noted significant geographic variation in the microbiota’s influence, underscoring the importance of contextualized interventions. Conclusions: The composition of the maternal microbiota has a major impact on neonatal immunity and the risk of early-life allergy. Adverse factors include cesarean birth, antibiotic exposure, and maternal stress, all of which have been associated with alterations in neonatal immunity. More studies are required to validate promising microbiota-targeted strategies and develop evidence-based guidelines to improve maternal and neonatal immune health.